Charles V's universal empire in the Compendio of Antonio Doria. Issue 3 (29th August 2017) - Salonia, Matteo
Abstract: Habsburg intellectuals claimed that Charles V (1500–1558) was chosen by God to coordinate the defence of Christendom against the Ottoman Empire and to take care of the spiritual wellbeing of all Christians by fighting heresy. The Genoese captain Antonio Doria ( c .1495–1577) was among the writers describing Charles as a pious and benevolent universal monarch and endorsing his military and political project. In the work entitled 'Compendio' (1571), Doria gives an account of the events taking place in the world during Charles's reign. This document is significant not only because Doria (with his more famous cousin Andrea) took part in several of the military episodes here recounted, but also because Genoa had joined the empire without losing its independence. Therefore, Antonio Doria's 'Compendio' represents an important source if we want to understand the reception of (and contribution to) sixteenth‐century imperial propaganda in the Italian context. After briefly presenting Doria's career and Genoa's republican culture, this article shows the global perspective of the text and argues that we can find in it an endorsement of Habsburg governance and an attempt to (re)order recent events within a universal, supranational framework. The final section briefly compares the 'Compendio' with two contemporary histories.